PENGARUH STATUS SOSIAL EKONOMI DAN TINGKAT PENDIDIKAN ORANG TUA TERHADAP MINAT STUDI LANJUT SISWA KELAS XII DI MA MIFTAHUL HUDA CENDONO PURWOSARI KABUPATEN PASURUAN - Ahmad Zaini; Sujito Sujito; Endah Andayani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
This research had the objective, namely: (1) clarify the influence of socio-economic status with the interests of further study of students of class XII in MA Miftahul Huda Cendono Purwosari Pasuruan (2) describe the effect of the education level of the parents with the interests of further study of students of class XII in MA Miftahul Huda Purwosari Cendono Pasuruan and (3) explain the influence of socio-economic status and educational level of the parents against the interest of further study of the students of class XII in MA Miftahul Huda Cendono Purwosari Pasuruan. The method used multiple linear regressions. In this study the samples used all students of class XII with totaling of 53 students. This was accordance with the title that will be examined; it was the interest of the students of class XII to continue the study. The results of this research indicated that: first, there was a positive and significant relationship between socio-economic statuses with the interests of further study of students of class XII in MA Miftahul Huda Cendono Purwosari Pasuruan. Based on the analysis of the correlation coefficient of rx1y , it was 2.435 (rx1y of 2,435> r table of 5% was 2,009). Secondly, there was a positive and significant relationship between the levels of education of parents with the interests of further studies of students of class XII in MA Miftahul Huda. Based on the analysis of the correlation coefficient of rx2y it was 3.074 (rx2y of 3.074> r tabel 5% was 2,009). Third, there was a positive and significant relationship between socio-economic status and educational level of the parents against the interests of further studies of students of class XII in MA Miftahul Huda Cendono Purwosari Pasuruan. Based on the analysis of the correlation coefficient (R) 0.742, coefficient of determination (R) 2 was 0.551 and F count was 48.152 (F count was 30.632 > F table was 5%, namely 3.183). From the results of a study, it can be concluded that there was significant influence between socio-economic status and educational level of parents against the interests of further studies of students of class XII in MA Miftahul Huda Cendono Purwosari Pasuruan